Kinerja Investasi Exchange Trade Fund di Indonesia - Gayatri, Gayatri; Sari Widhiyani, Ni Luh (E-Jurnal Akuntansi; Vol 31 No 7 (2021)DO - 10.24843/EJA.2021.v31.i07.p02, 2021)
The aim of this research is to obtain empirical evidence about the effect of stock selection skills, market timing ability, fund size and fund age on the performance of exchange trade funds. The population in this study are all exchange trade fund investment products listed on the Indonesia Stock Exchange from 2017 to 2019. The sampling technique uses purposive sampling. To test the hypothesis, multiple linear regression analysis was used. This study proves that stock selection skills have a positive effect on the performance of exchange trade funds in Indonesia. Meanwhile, market timing ability, fund size and fund age do not have a positive effect on the performance of exchange trade funds in Indonesia. The reason is that only one investment manager PT. Indo Premier Investment Management which is always active in trading exchange trade funds in Indonesia. This research has implications for the more active investment managers in offering exchange trade fund products to attract investors because they are able to survive in times of crisis. Keywords: Exchange Trade Funds; Investation.